2014
DOI: 10.1177/183693911403900309
|View full text |Cite
|
Sign up to set email alerts
|

Family Day Care Educators' Knowledge, Confidence and Skills in Promoting Children's Social and Emotional Wellbeing: Baseline Data from Thrive

Abstract: THIS PAPER PRESENTS BASELINE data from Thrive, a capacity-building program for family day care educators. Educators completed a self-report survey assessing knowledge and confidence in promoting children's social and emotional wellbeing. An in-home observation was used to assess care quality. Twenty-four educators responded to the survey (40 per cent response rate). They had an average of nine years' experience and 82 per cent held childcare qualifications. Educators reported knowledge of, on average, three ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…To be eligible for the study, centres had to provide care for a minimum of 15 preschool aged (3–5 years) children with the classification of day care program, as opposed to family day home or after school care program. A sample size of 100–200 participants was identified for phase 1 based on an anticipated response rates ranging from 40 to 80% [6, 24–26]. In phase 2, a convenience sample of ECEC centres, with the same criteria as described above were recruited from one large urban location for director participation and centre-based direct observation.…”
Section: Methodsmentioning
confidence: 99%
“…To be eligible for the study, centres had to provide care for a minimum of 15 preschool aged (3–5 years) children with the classification of day care program, as opposed to family day home or after school care program. A sample size of 100–200 participants was identified for phase 1 based on an anticipated response rates ranging from 40 to 80% [6, 24–26]. In phase 2, a convenience sample of ECEC centres, with the same criteria as described above were recruited from one large urban location for director participation and centre-based direct observation.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies (e.g., Davis, 2014;Desta, 2017;Isaksson et al, 2017) have investigated early childhood educators' mental health knowledge in specific countries around the world. Understanding early childhood educators' ability to identify and respond to mental health needs in early childhood is an essential step toward lessening the impact of untreated mental health needs among young children.…”
Section: Early Childhood Educator's Mental Health Knowledgementioning
confidence: 99%
“…Furthermore, sufficient resources (child wellbeing plans, decision making plans and information) and confidence are both key to FDC educators' propensity for help-seeking. Davis et al (2014) found that FDC educators with concerns about a child's wellbeing would wait until the situation became more serious before seeking support, fearing they did not have the confidence or the resources to handle it appropriately. Building the confidence of FDC educators and equipping them with appropriate resources can thus help them to support children early on before their situation progresses to crisis point.…”
Section: Supporting Children's Mental Health and Wellbeingmentioning
confidence: 99%